Hubungan Manajemen Pelayanan Terpadu Satu Pintu dengan Inovasi Layanan Administrasi - Azzahra, Siti Fatimah; Sanusi, Hary Priatna; Kasmin, Kasmin (MES Bogor, 2024)
One-Stop Integrated Service as a process of simplifying administrative services controlled by a management system as a form of administrative service innovation. This study aims to examine the relationship between One-Stop Integrated Service Management and administrative service innovation in Education unit services at the Ministry of Religious Affairs of West Jakarta City. The research was carried out with a quantitative approach with the type of survey research. The research data was collected by questionnaire method. The population in this study was visitors to the One-Stop Integrated Service Education service unit with incidental sampling techniques. Data analysis techniques use correlation analysis. The results showed that: (1) One-Stop Integrated Service Management has an average calculation of 2.54 so that it can be rated high. (2) Administrative service innovation has an average of 3.08, which is in the high category. (3) The relationship between One-Stop Integrated Service Management and Administrative Service Innovation. The value of the relationship between the two variables is 0.521, the results show that the correlation is quite strong and positive value between the two variables. This research shows that One-Stop Integrated Service Management is related to administrative service innovation.